Тhe phenomenon of interdisciplinarity: cognitive science - Dobrovolska, O. V. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
Тhe phenomenon of interdisciplinarity is considered as a factor of formation of post-nonclassical science at the example of cognitive science. The structure and nature of the relationships within cognitive science are analysed at various stages of its development: multidisciplinary, interdisciplinary, on the way to transdisciplinarity. The role of philosophy in the development of cognitive science as a complex systemis revealed.